Development of a pilot scale high pressure food processing system - Elamin, Wael Mohamed Abdalla (2016)
High-Pressure Processing (HPP) is a non-thermal widely recognized pasteurization method to inactivate microorganisms and enzymes to prolong product shelf life instead of the conventional thermal preservation.However, unlike thermal methods, it can maintain the quality and keep the original nutrients, vitamins, flavor, and appearance as well. Such technology can be introduced to the country, to replace the current traditional methods of processing of many local food products. Although, high pressure processing has gained the interest of many manufacturers in the food industry, the cost of HPP equipment is considered high, and therefore, there are voices calling for new equipment.The groundwork of this effort is to design, develop, and test of pilot-scale high-pressure food processing equipment that serve both small businesses and as a laboratory unit. The fabricated system comprises two pressurizing systems as well as two pressure vessels and their connections.Experimental work and testing of the fabricated machine was extensively done and further testing of different processing pressures on different types of local food,allocating the quality attributes and improvement were also made. It seeks the better understanding of work of a pilot plant unit, both in its ability to reduce microorganisms and to find the effect of changes in the physical and quality attributes of treated food,namely Oil Palm fruit, Durian mash, Blood Cockles, Shrimps and Mud Crabs.The testing of this HPP machine resulted in some significant contributions, findings, and observation and valuable discussions were conducted. A significant shelf life resulted in the Oil Palm fruit with an extension up to one year with 310 MPa of pressure. Blood Cockles, Shrimps and Mud Crab improved their separation and sensory quality at 345 MPa, while Durian mash and Blood Cockles’ microbial safeties were enhanced. HPP has reduced the microbial load of Durian mash from 5.9×104 to 4.8×102 CFU/g, whereas in the case of Blood Cockles the initial microbial load of 5.7×104 CFU/g was totally inactivated by 240 MPa of pressure and above. This work offers insight into upcoming areas of research opportunity particularly in the local food industry.